Management of primary infertility in a patient with Kartagener’s syndrome: a case report - Yaramareddy, Swapna; Valluri, Lenin Babu; Sardena, Siyonu Kumari; Bhukya, Nom Kumar Naik; Naik, Menavath Tulasi Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Kartagener’s syndrome (KS) is a subgroup of primary ciliary dyskinesia (PCD), an autosomal recessive hereditary condition characterised by chronic sinusitis, bronchiectasis, and situs inversus. The fundamental pathophysiologic issue in Kartagener’s syndrome is abnormal ciliary structure or function, which results in decreased ciliary motility. The patient in the present case was a 31-year-old female with a twelve-year history of primary infertility. In vitro fertilization and embryo transfer (IVF-ET) was performed and the patient conceived successfully. PCD should be strongly considered in women whose main infertility is accompanied by persistent respiratory symptoms. In women with PCD, superovulation and intrauterine insemination would not improve the likelihood of conception. In infertile women with PCD, IVF-ET is considered to be the best therapeutic option.